Civilization in the epoch of changes: search for new development strategies - Stepin, Vyacheslav S. (Journal of the Belarusian State University. Sociology, 2019)
Modern civilization is ascertained to have entered the stage of instability and crisis followed, as a rule, by fundamental qualitative systemic changes. When analyzing modern changes in civilizational development, it requires considering the global civilizational changes as a complex systemic integrity. Such a transformation is expressed in the conception of types of civilizational development, each type of civilization development be considered in its historical evolution. The problem of new development strategies that could overcome the cardinal global crises entailing the destruction of civilization and even self-destruction of mankind is raised. These strategies suggest a rethinking of the typological core of the sociocultural genome of modern civilization. The importance of singling out and fixing as an initial boundary of these searches the ideal of preserving the mankind as a special subsystem of the biosphere and the biosphere itself as a complex evolving value system is underlined.